2017
DOI: 10.1186/s12977-017-0330-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of small molecule modulators of HIV-1 Tat and Rev protein accumulation

Abstract: BackgroundHIV-1 replication is critically dependent upon controlled processing of its RNA and the activities provided by its encoded regulatory factors Tat and Rev. A screen of small molecule modulators of RNA processing identified several which inhibited virus gene expression, affecting both relative abundance of specific HIV-1 RNAs and the levels of Tat and Rev proteins.ResultsThe screen for small molecules modulators of HIV-1 gene expression at the post-transcriptional level identified three (a pyrimidin-7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…Rev is critical in mediating nuclear export of incompletely-spliced (US/SS) HIV-1 RNAs to the cytoplasm while Tat is essential as a transactivator of viral transcription [35][36][37][38]. These results (and data on HIV-1 RNAs and SR proteins described below) are in mark contrast to previous HIV-1 RNA-processing inhibitors reported, suggesting a novel mechanism of action [27,28,33,[39][40][41][42][43].…”
Section: Compound 5342191 Suppresses the Expression Of Essential Hiv-mentioning
confidence: 65%
See 2 more Smart Citations
“…Rev is critical in mediating nuclear export of incompletely-spliced (US/SS) HIV-1 RNAs to the cytoplasm while Tat is essential as a transactivator of viral transcription [35][36][37][38]. These results (and data on HIV-1 RNAs and SR proteins described below) are in mark contrast to previous HIV-1 RNA-processing inhibitors reported, suggesting a novel mechanism of action [27,28,33,[39][40][41][42][43].…”
Section: Compound 5342191 Suppresses the Expression Of Essential Hiv-mentioning
confidence: 65%
“…In comparison with other HIV-1 RNA processing inhibitors, 5342191 induces fewer alterations to host AS events (0.25-0.67% change and r = 0.97 compared to DMSO, resp., in Fig 2E and 2F) than those detected for the CS digitoxin (20.6%) and ABX464 (r = 0.89) by RNA-Seq or chlorhexidine (8.1%) by exon microarray [41,72,73]. 5342191-induced changes in AS convert to only 0.46% of host genes becoming DE by ïżœ 2 fold in cells ( Fig 2G) which is lower than those reported for other HIV-1 RNA processing inhibitors at this threshold (and same cell type): 1C8 (0.95%) and 9147791 (0.75%) [40,42]. Although not previously reported for any other HIV-1 RNA processing inhibitors, 5342191 perturbs the abundance of only 0.02-0.34% of host proteins by ïżœ 1.5-2.0 fold ( Fig 3D) which is over 2.2-6.5-fold lower than the changes observed in 9147791-treated cells at this cut-off (0.13-0.75%, S9C Fig).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Thereby, inhibiting Tat activity results in hindering the positive feedback loop required for efficient HIV-1 transcription. Interestingly, Tat has been shown to be sensitive to proteasome degradation (39)(40)(41)(42)(43)(44)52). We observed that Tat expression was inversely proportional to KAP1 expression level suggesting that KAP1-mediated repression of Tat function results from Tat degradation.…”
Section: Discussionmentioning
confidence: 69%
“…Among the mechanisms controlling protein half-life in eukaryotic cells, the degradation via the proteasome pathway has been long studied. Interestingly, Tat has been described to be directed towards proteasome degradation (39)(40)(41)(42)(43)(44). To determine whether the reduced expression of Tat in the presence of KAP1 is related to proteasome degradation, we quantified Tat expression levels in the presence of KAP1 and the proteasome inhibitor MG132, (Figure 8 D).…”
Section: Kap1 Promotes Tat Degradation By the Proteasome Pathwaymentioning
confidence: 99%